TINJAUAN HUKUM PIDANA TERHADAP MOTIF PEMALSUAN TANDA TANGAN DAN STEMPEL YANG DILAKUKAN PEJABAT DESA (STUDI KASUS DI DESA SAENAMA KECAMATAN RINHAT KABUPATEN MALAKA) - Yohana Elma Klau; Deddy R Ch Manafe; Adrianus Djara Dima (Petitum Law Journal, 2026)
This study evaluates the criminal law perspective on the forgery of signatures and stamps committed by Saenama Village Officials, Malaka Regency, in 2022, to analyze the legal implications and criminogenic factors underlying the act of forgery committed by village officials. The method used in this study is an empirical approach by utilizing primary data through interviews and secondary data derived from legal documents. The research findings indicate that the forgery was carried out in order to take village funds illegally, and was triggered by internal factors such as personal motives, lack of knowledge of the law, abuse of power, and economic pressure, as well as external factors caused by weak supervision. Using a juridical-empirical approach, this study examines how the creation of fake documents, forged signatures, and counterfeit stamps reflects systemic weaknesses in local governance and legal accountability.This action not only violates Article 263 of the Criminal Code concerning forgery, but is also included in the category of corruption crimes based on the Corruption Law with broad impacts, namely losses to the state, disruption of village development, and reduced public trust. This study concludes that strengthening supervision mechanisms, enhancing legal education for village officials, and implementing transparent governance practices are essential strategies to prevent the recurrence of similar fraudulent acts.